Easy and rapid method for the determination of gene expression in cumulus cells incubated for oocyte maturation - Yamashiro Hideaki; Wang Haifeng; Kumamoto Kanako; Terada Takato (BMC, 2005)
Abstract Background The objectives of this study were to develop an easy and rapid method for measuring gene expression in a small number of cells by real-time PCR without RNA extraction and purification, and to use this method to determine more precisely IGF-I gene expression in the cumulus cells surrounding oocytes. Methods First, after small numbers of cumulus cells were lysed in cell lysis buffer, they were digested with various concentrations of DNase I for different periods at 37°C to determine the optimal conditions for digestion of genomic DNA in the lysate. Since nonspecific amplification was liable to occur when the non-purified RT product of the cell lysate was used for real-time PCR with the given primers, the optimal conditions for Mg2+ and annealing temperature were well investigated. Further, to create the same conditions as in the actual sample reaction for measurement by real-time PCR, RT-minus product was added to the reaction mixture of the standard curve, and then the amplification efficiency was assessed. Next, IGF-I gene expression in cumulus cells collected from cumulus oocyte complexes (COCs) every 4 h during maturation was determined using the developed method. Results The optimal conditions for measuring gene expression using the cell lysate from a small number of cells were as follows: incubation of the cell lysate with 0.16 U/microL DNase I with 10 U/microL for 30 min, an Mg concentration of 1.5 mM for amplification of target gene by real-time PCR using RT-product of the cell lysate. When the RT-minus products added to the reaction mixture for the standard curve, which was prepared for purified 18SrRNA plasmid, the PCR efficiency was similar between the sample and the standard. The IGF-I gene expression in the cumulus cells was elevated up through the first 8 h of the culture and then declined gradually by the end of maturation, with the maximal gene expression (778-fold) seen at 8 h. Conclusion It can be concluded that the method developed here, in which equivalent to cumulus cells collected from 0.03-0.075 COCs were employed per reaction, permits rapid and easy determination of target gene expression in a limited number of cells using real-time PCR without RNA extraction.